Can population differences in chemotherapy outcomes be inferred from differences in pharmacogenetic frequencies - Loh, M.; Chua, D.; Yao, Y.; Soo, R.; Garrett, K.; Zeps, Nikolajs; Platell, C.; Minamoto, T.; Kawakami, K.; Iacopetta, B.; Soong, R. (2013)
Inter-ethnic differences in drug handling and frequencies of pharmacogenetic variants are increasingly being characterized. In this study, we systematically assessed the feasibility of inferring ethnic trends in chemotherapy outcomes from inter-ethnic differences in pharmacogenetic variant frequencies. Frequencies of 51 variants and chemotherapy outcomes of East Asian and Caucasian colorectal cancer patients on standard chemotherapy regimens were summarized by meta-analyses, and variant frequencies were validated by MassARRAY analysis. Inferences of relative chemotherapy outcomes were made by considering minor allele function and population differences in their frequency. Significant population differences in genotype distributions were observed for 13/23 (60%) and 27/35 (77%) variants in the meta-analyses and validation series, respectively. Across chemotherapy regimens, East Asians had lower rates of grade 3/4 toxicity for diarrhea and stomatitis/mucositis than Caucasians, which was correctly inferred from 13/18 (72%, P=0.018) informative genetic variants. With appropriate variant selection, inferring relative population toxicity rates from population genotype differences may be relevant.